Fighting Sharka in Peach: Current Limitations and Future Perspectives - Cirilli, Marco; Geuna, Filippo; Babini, Anna R.; Bozhkova, Valentina; Catalano, Luigi; Cavagna, Beniamino; Dallot, Sylvie; Decroocq, Véronique; Dondini, Luca; Foschi, Stefano; Ilardi, Vincenza; Liverani, Alessandro; et al. (Frontiers in Plant Science, 2016)
Sharka, caused by Plum Pox Virus (PPV), is by far the most important infectious disease of peach [P. persica (L.) Batsch] and other Prunus species. The progressive spread of the virus in many important growing areas throughout Europe poses serious issues to the economic sustainability of stone fruit crops, peach in particular. The adoption of internationally agreed-upon rules for diagnostic tests, strain-specific monitoring schemes and spatial–temporal modeling of virus spread, are all essential for a more effective sharka containment. The EU regulations on nursery activity should be modified based on the zone delimitation of PPV presence, limiting open-field production of propagation materials only to virus-free areas. Increasing the efficiency of preventive measures should be augmented by the short-term development of resistant cultivars. Putative sources of resistance/tolerance have been recently identified in peach germplasm, although the majority of novel resistant sources to PPV-M have been found in almond. However, the complexity of introgression from related-species imposes the search for alternative strategies. The use of genetic engineering, particularly RNA interference (RNAi)-based approaches, appears as one of the most promising perspectives to introduce a durable resistance to PPV in peach germplasm, notwithstanding the well-known difficulties of in vitro plant regeneration in this species. In this regard, rootstock transformation to induce RNAi-mediated systemic resistance would avoid the transformation of numerous commercial cultivars, and may alleviate consumer resistance to the use of GM plants.